Modulating the activities of chloroplasts and mitochondria promotes adenosine triphosphate production and plant growth - Chia P. Voon; Yee-Song Law; Xiaoqian Guan; Shey-Li Lim; Zhou Xu; Wing-Tung Chu; Renshan Zhang; Feng Sun; Mathias Labs; Dario Leister; Mathias Pribil; Marie Hronková; et al. (Quantitative Plant Biology, 2021)
Efficient photosynthesis requires a balance of ATP and NADPH production/consumption in chloroplasts, and the exportation of reducing equivalents from chloroplasts is important for balancing stromal ATP/NADPH ratio. Here, we showed that the overexpression of purple acid phosphatase 2 on the outer membranes of chloroplasts and mitochondria can streamline the production and consumption of reducing equivalents in these two organelles, respectively. A higher capacity of consumption of reducing equivalents in mitochondria can indirectly help chloroplasts to balance the ATP/NADPH ratio in stroma and recycle NADP+, the electron acceptors of the linear electron flow (LEF). A higher rate of ATP and NADPH production from the LEF, a higher capacity of carbon fixation by the Calvin–Benson–Bassham (CBB) cycle and a greater consumption of NADH in mitochondria enhance photosynthesis in the chloroplasts, ATP production in the mitochondria and sucrose synthesis in the cytosol and eventually boost plant growth and seed yields in the overexpression lines.